Faktor-Faktor Yang Berhubungan Dengan Kejadian Stunting Pada Balita Di Dusun Kelapa Dua Kecamatan Kairatu Kabupaten Seram Bagian Barat - Herlien Sinay (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
Stunting is a condition of failure to thrive in children due to chronic malnutrition that results in a child's height not in accordance with their age. Stunting is not only caused by one factor but by multifactors. This study aims to determine the relationship between maternal education level, maternal knowledge, exclusive breastfeeding, complementary feeding and family economic status with the incidence of stunting in Kelapa Dua Hamlet, Kairatu District, West Seram Regency. The research design used was cross sectional. This study consisted of 100 samples with probability sampling technique. Data analysis was performed with the Chi-square test. The results showed that there was a relationship between the incidence of stunting and the level of maternal education (p-value = 0.000), maternal knowledge (p-value = 0.000), exclusive breastfeeding (p-value = 0.001) and complementary feeding (p-value = 0.000). However, family economic status (p-value = 0.511) has no relationship with the incidence of stunting in toddlers in Kelapa Dua Hamlet, Kairatu District, West Seram Regency.